If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=8(2x+3)-17
We move all terms to the left:
9-(8(2x+3)-17)=0
We calculate terms in parentheses: -(8(2x+3)-17), so:We get rid of parentheses
8(2x+3)-17
We multiply parentheses
16x+24-17
We add all the numbers together, and all the variables
16x+7
Back to the equation:
-(16x+7)
-16x-7+9=0
We add all the numbers together, and all the variables
-16x+2=0
We move all terms containing x to the left, all other terms to the right
-16x=-2
x=-2/-16
x=1/8
| 9=8(2x+3)-16 | | f-32=1.8*3 | | f-32=1.8*8 | | -7*x+30=-5 | | 3w-14=28 | | 5(a-2.95)=47.75 | | 8p-11=13 | | 3x-30=8x | | 4x+14=50−2x | | 18-t=24 | | 15x-6=6x-15 | | 1+2t-t-3+3t=0 | | 8x+4=3(x-1)+2 | | y=0.04*27*54 | | y=(1/27)*(27)*(54) | | y=(1/27)*27*54 | | y=1/27*27*54 | | 14x+1+15x-2=180 | | 6=k*9*18 | | (8x+7)/6=(5x+2)/7 | | 5p+28+12p=180 | | x2+2x+2=0 | | 1+11x=-39 | | -1.88=(x-15)/2.5 | | (x+2)3-x3=56 | | (18-x)2=(16-x)2+(9-x) | | 5x^2=21x+4 | | a/6+2=11 | | 10=5x2 | | 7x-36=-15 | | (2-x)(5x+1)-(3+x)(x-1)+8x2-15x+3=0 | | 6(3w+4)/5=-1 |